Experimental and modelling analysis of efficiency enhancement in a liquid piston gas compressor using metal plate inserts for compressed air energy storage application. (November 2021) - Khaljani, M.; Vennard, A.; Harrison, J.; Surplus, D.; Murphy, A.; Mahmoudi, Y.
Highlights: Detailed flow and thermal fields in a liquid piston compressor are analysed using experimental and numerical analyses. Aluminium parallel plates are used for increasing the compression efficiency. The maximum increase in the compression efficiency is 8% at slow compression. The optimum plate height for maximum efficiency is 0.9 m for all plate thicknesses. Abstract: In this work, experimental and modelling analyses are performed in order to improve the compression efficiency of a Liquid Piston Gas Compressor (LPGC), which utilizes a column of water for air compression. Due to low cost and easy manufacturing, aluminium parallel plates are used as the heat exchanger inside the LPGC to absorb the thermal energy from the compressed air and hence increase the efficiency of the compressor. A comprehensive set of experimental and numerical analyses are performed to gain deep insight into the flow and thermal characteristics of the air and water in the LPGC with plate inserts. A LPGC prototype including a steel cylinder with a height of 1.1 m and a diameter of 0.08 m is developed and experimental data is collected for air compression from 8 bar to 40 bar. Experiments are performed for three plate inserts with different heights of 0.2 m, 0.35 m and 0.5 m. Experimental data is acquired for 3 different water flow rates of 0.0005 m 3 s −1, 0.0007 m 3 s −1 and 0.0008 m 3 s −1 equivalent to compression times of 1.7 s, 2.6 s and 3.5 s, respectively. To gain further understanding of the flow and heat transfer characteristics inside the LPGC, three-dimensional modelling is performed by solving unsteady Reynolds-Averaged Naiver Stokes (RANS) equations and deploying the Volume of Fraction (VOF) approach for tracking the water-air interface in the LPGC cylinder. Experimental results show that in comparison to the no-insert LPGC case, the air temperature at the end of the compression can be reduced by about 50 K, 75 K, and 82 K with the inclusion of plate inserts with the height of 0.20 m, 0.35 m and 0.5 m, respectively. This leads to an increase in the LPGC compression efficiency by about 3%, 4% and 8%, respectively. The modelling tool validated against the experimental data, revealed that for a fixed number of plates in the LPGC, increasing the thickness of the plates, increases the compression efficiency. Additionally, the parametric study performed by the modelling tool showed that for a fixed plate thickness, increasing the plate height up to an optimum value, compression efficiency increases. After, further increase in the plate height, decreases the compression efficiency. For the LPGC geometrical property and compression conditions studied here, the optimum plate height, which maximizes the efficiency, is found to be 0.9 m for all plate thicknesses studied.